Moneda “Latín”, la nueva moneda de Latinoamérica - Díaz Ojeda Nicolás (Universidad Antonio Nariño, 2024)
The main objective of this project is to share with you my ambitious idea, which may be considered as utopian. However, some years ago the people from Europe saw the Euro as an utopian currency and we know what it already is and how it helped them to be just above the international one (Dollard).